Effect of dietary inclusion of ginger (zingiber officinale) dried with different methods on perfonnance and gut microbial population of broiler chicks (2016)
Effect of dietary inclusion of differently processed ginger on performance and microbial population of broiler chicks were investigated in a 52-days feeding trial. A total of three hundred one-day old (arbor acre) broiler chicks were used for the experiment, the birds were allotted into ten dietary treatments of five replicates and six birds per replicate in a 3x3 factorial arrangement of completely randomized design. Weights of the birds were taken weekly throughout the experimental period. Birds were fed ad-libitum such that diet 1 was the basal diet (BD) without ginger, diets 2, 3 and 4 were BD+ sundried ginger at 1, 1.5, 2% inclusion levels respectively, diets 5, 6 and 7 were BD+ air- dried ginger at 1, 1.5 and 2% inclusion levels respectively, diets 8, 9 and 10 were BD+ oven-dried ginger at 1, 1.5 and 2% inclusion level respectively. On day 52 of the experiment, the birds were slaughtered. Sections of the ileum was cut and aseptically emptied into a sterile bottle for microbial analysis. Broilers fed diets containing ginger had no significant (P> 0.05) differences on the average initial body weight, average final body weight and average daily feed intake. Although the birds fed with diet containing oven-dried ginger at 2% inclusion level had the least (P>0.05) numerical difference of the average daily feed intake. The average body weight gain and feed conversion ratio (FCR) were not significant across the dietary treatments. Birds fed diet without ginger had higher body weight gain and best feed conversion ratio (P<0.05). The total Aerobic and coliform microbial counts of broilers were not significantly (P>0.05) affected by the dietary treatments. Although the total aerobic microbial count was reduced in birds fed diets containing ginger when compared with the control.